Market Assessment on White Oyster Mushroom in Luzon, Philippines - Iglesia, Maria Joy Casano (Journal of Management Studies and Development, 2025)
This study analyzed the market for white oyster mushrooms and evaluated labeling, packaging, and compliance. It focused on growers and sellers in Luzon, Philippines, specifically Region III, IV-A, and Bicol Region. The market was assessed based on consumer preferences, packaging, labeling, pricing, aesthetics, and product quality. Production factors included human resources, logistic support, product freshness, quality standards, and market opportunities. Findings revealed a high demand for fresh mushrooms, often used as meat substitutes. Top by-products in demand were mushroom chicharron, sisig, pickled mushrooms, lumpia, embutido, tempura, and flavored ice cream. Consumers were satisfied with product prices and taste but indicated the need for improved packaging, labeling, and quality compliance. Producers recognized high market potential and agreed on the need for government and business strategy support. However, challenges included limited logistic support, freshness maintenance, and quality compliance. The study concluded that there is a strong market opportunity for white oyster mushrooms and their by-products, but improvements in packaging, labeling, and quality standards are essential.